Arbitration And the Efforts of Advisory (Ifta) Committees Concerning the Settlement of Disputes in Kurdistan Region –Iraq: An analytical legal study - Sherzad Azeez Sulaiman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Advisory (Ifta) committees in the Kurdistan Region-Iraq have multiple activities in Kurdistan society this research tries to study specific issues of these activities focused on : (Arbitration and the efforts of advisory (Ifta) committees concerning the settlement of disputes in Kurdistan Region – an Analytical legal study –) In order to answer a number of questions related to the settlement of disputes under the private law in general, whether civil or personal status, especially those cases which could be legally described as arbitration. It is also tries to compare those efforts and the procedures followed by the Advisory Committees with regard to them with the legal texts on this issue. The importance of this research is that it is trying to reach a set of legal consequences in this regard and on the premise that these efforts are arbitration, it tries to find out the compatibility of the procedures followed by these committees in their work by comparing them with the legal texts in that case, to arrive at the end of the research to results lead to improve the role and outcomes of such committees in justice within the society.